New insights into the efficient secretion of foreign protein in Bacillus subtilis via Ribo-seq and RNA-seq integrative analyses - Huabiao Miao; Xia Xiang; Ling Cheng; Qian Wu; Zunxi Huang (BMC Microbiology)
Abstract Background As an important prokaryotic model organism, Bacillus subtilis has been widely used in the industrial production of a variety of target products. The efficient secretion of target products has always been the main purpose of industrial microbial technology. The modification of gene regulatory networks is an important technical means to construct a factory of microbial cells that efficiently secretes target products. However, the regulatory network of the efficient expression of foreign genes in B. subtilis has not been studied at the translation level. Results In this study, Ribo-seq and RNA-seq technology were used to study the changes in differentially expressed genes during the efficient secretion of the protease PB92 by B. subtilis WB600, and the results revealed the gene regulatory network related to efficient secretion of foreign protein. The results revealed that the correlation between the differentially expressed genes of B. subtilis at the transcription and translation levels was only 0.5354. Forty-one common (transcription and translation) and 436 unique (translation) key differential gene sets that may be related to the efficient secretion of foreign proteins were revealed. KEGG enrichment analysis of these key gene sets revealed that they were involved mainly in the cell motility and central metabolic regulatory network of B. subtilis. Conclusion Our study provides important guidance for the construction of cell factories and metabolic networks for the efficient secretion of target products by B. subtilis.